Responsible investing: Costs and benefits for university endowment funds - Aragon, George O.; Jiang, Yuxiang; Joenväärä, Juha; Tiu, Cristian Ioan (Journal of Financial Economics, 2025)
We examine the adoption rates of responsible investment (RI) policies among university endowments. Adoption rates are higher among universities that face stakeholder pressure and are donation-dependent. Policy adoption predicts greater abnormal donations totaling 12 % of endowment assets, especially from “socially conscious” donors and during periods of higher media attention to climate change. Universities also experience greater student applications following adoptions. RI endowments have greater management costs, greater return volatility, and similar overall asset growth (donations plus net-of-cost investment income) compared to non-RI endowments. We conclude that RI policies are an important part of the optimal contract between universities and their stakeholders.